2017
DOI: 10.1016/j.neuroimage.2016.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Shared orthographic neuronal representations for spelling and reading

Abstract: A central question in the study of the neural basis of written language is whether reading and spelling utilize shared orthographic representations. While recent studies employing fMRI to test this question report that the left inferior frontal gyrus (IFG) and ventral occipitotemporal cortex (vOTC) are active during both spelling and reading in the same subjects (Purcell et al., 2011a; Rapp and Lipka, 2011), the spatial resolution of fMRI limits the interpretation of these findings. Specifically, it is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 113 publications
(187 reference statements)
5
27
0
Order By: Relevance
“…It has been shown that competition between representations in the linguistic system (Zhuang, Tyler, Randall, Stamatakis, & Marslen-Wilson, 2014) and increased duration of certain stages of processing (Coull, Charras, Donadieu, Droit-Volet, & Vidal, 2015) lead to increases of the BOLD signal in the regions where the relevant information is processed. In the left FuG, the increase is probably related to the competition between representations and/or lengthened processing in orthographic long-term memory (Purcell, Jiang, & Eden, 2017;Purcell et al, 2011;Rapp & Dufor, 2011;Rapp et al, 2016). The left IFG showed the most reliable pattern of differences between regular and irregular words in the 3 models tested.…”
Section: Evidence For Continuous Flow Of Information Between the Orthmentioning
confidence: 89%
“…It has been shown that competition between representations in the linguistic system (Zhuang, Tyler, Randall, Stamatakis, & Marslen-Wilson, 2014) and increased duration of certain stages of processing (Coull, Charras, Donadieu, Droit-Volet, & Vidal, 2015) lead to increases of the BOLD signal in the regions where the relevant information is processed. In the left FuG, the increase is probably related to the competition between representations and/or lengthened processing in orthographic long-term memory (Purcell, Jiang, & Eden, 2017;Purcell et al, 2011;Rapp & Dufor, 2011;Rapp et al, 2016). The left IFG showed the most reliable pattern of differences between regular and irregular words in the 3 models tested.…”
Section: Evidence For Continuous Flow Of Information Between the Orthmentioning
confidence: 89%
“…Its role in orthographic specific processing has been reported in both the neuroimaging and lesion literature. In the neuroimaging literature, the left IFJ has been found to be functionally active in both reading and spelling, along with the left FG (Purcell, Jiang, & Eden, 2017; Purcell, Napoliello, et al, 2011; Rapp & Lipka, 2011). The lesion literature includes reports that damage to this region is associated with deficits in orthographic lexical processing in spelling (Hillis, Chang, Breese, & Heidler, 2004; Rapp et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used spelling judgment tasks in which participants were required to press buttons to report the correct spelling of words or letters presented visually or auditorily. Several brain regions have been found to subserve the retrieval of orthographic codes, including the left posterior inferior frontal gyrus (Rapp and Lipka, 2011 ; Purcell et al, 2017 ), the fusiform gyrus (Kronbichler et al, 2004 ; Philipose et al, 2007 ; Rapp and Dufor, 2011 ), the supplementary motor area (SMA) (Purcell et al, 2017 ), and the superior parietal lobule/inferior parietal sulcus (Purcell et al, 2011 ). However, such spelling judgment tasks are inherently different from actual writing.…”
Section: Introductionmentioning
confidence: 99%